Case report: Early acute myocarditis after radiation therapy for breast cancer: A case presentation and review of literature - Sharifkazemi, Mohammadbagher; Elahi, Mahsa; Sayad, Masoud (Frontiers in Cardiovascular Medicine, 2023)
Breast cancer is the most commonly diagnosed cancer in women worldwide, and with the increased survival of patients by novel treatments, the frequency of complications of cancer treatments rises. Radiotherapy, especially on the chest wall, can damage different cardiac structures. Radiotherapy-induced cardiomyopathy mainly occurs over 10 years after breast cancer treatment; however, there is a gap in the literature on acute myocarditis following radiotherapy. Here, we present a 54-year-old woman who developed acute myocarditis shortly after 25 sessions of radiotherapy with 50 Gy of radiation, successfully diagnosed with the use of speckle tracking echocardiography (STE) and cardiac magnetic resonance (CMR), and responded to the medical treatment with relative clinical improvement until the final follow-up. This case suggests the necessity of detailed examination of patients after radiotherapy, not only for chronic occurrence of cardiomyopathy but also for acute myocarditis. Although STE and CMR resulted in accurate diagnosis, in this case, further studies are required to determine the diagnostic accuracy of these two imaging methods compared with other imaging modalities in such patients and investigate the best diagnostic tool and therapeutic approach for these patients.